Tourism sector in Bukittinggi: Analysis of tourism competitiveness before and after COVID-19 - Syawal, Fadhilah; Satrianto, Alpon (Optimum: Jurnal Ekonomi dan Pembangunan, 2024)
The tourism industry, a crucial service sector, has been significantly impacted by the global pandemic, Covid-19. This impact has not only affected the development of tourism but also the regional economy. Bukittinggi, a key tourism city in West Sumatra, now more than ever, requires a competitive analysis to ensure its continuous growth. This research is aimed at analyzing and comparing Bukittinggi's tourism competitiveness before and after Covid-19. The research, a quantitative descriptive study with an exploratory research design, utilizes Competitiveness Monitor analysis. The data, sourced from BPS, BKD, and Bukittinggi Tourism Office, is secondary. The research results present the comparative results of the Tourism Competitiveness Analysis of Bukittinggi city as follows: a). PCI before Covid-19 was greater than after Covid-19; b). EI competitiveness before Covid-19 was higher than after Covid-19; c). HTI after Covid-19 was higher than before Covid-19; d). IDI after Covid-19 is higher than before Covid-19; e). OI after Covid-19 is higher than before Covid-19; 6). HRI after Covid-19 is higher than before Covid-19; f). TAI Value competitiveness index after Covid-19 is higher than before Covid-19; g). SDI before and after Covid-19 is equal. This research explains comparison of Bukittinggi's tourism competitiveness before and after Covid-19. The contribution of study are: a). consideration on improving tourism sites; b). Tourism management needs to be carried out in an integrated manner; and c). The government is expected to conduct more repairs and maintenance on tourism locations to increase visitor comfort when traveling.